A review: Reaction mechanism and strength of slag and fly ash-based alkali-activated materials. (4th April 2022) - Sun, Beibei; Ye, Guang; de Schutter, Geert
Highlights: The effects of particle size, chemical composition, glassy phase content on the reactivity of slag and fly ash are investigated. The physical and chemical requirements of slag and fly ash for the stable performance of AAM are summarized. The reaction mechanisms of BFS-AAM, FA-AAM, and BFS/FA-AAM are clarified. The reaction products of BFS-AAM, FA-AAM, BFS/FA-AAM are studied. The factors affecting the strength of BFS-AAM, FA-AAM, BFS/FA-AAM are explored and influencing mechanisms are discussed. Abstract: Alkali-activated materials (AAM) are known to be environmentally friendly alternatives to cement-based materials because they can potentially reduce greenhouse gas emissions and reutilize industrial by-products/wastes. To study the factors influencing the strength of slag based alkali-activated materials (BFS-AAM), fly ash based alkali-activated materials (FA-AAM), slag, and fly ash-based alkali-activated materials (BFS/FA-AAM), and clarifying their reaction mechanisms, this paper reviews current knowledge about the mechanical properties and the reaction mechanisms of BFS-AAM, FA-AAM, and BFS/FA-AAM. The precursor requirements and the strength control factors are summarized. The control factors for the strength of BFS/FA-AAM are the BFS/binder ratio, the Na2 O/binder ratio, the SiO2 /Na2 O ratio, and the w/binder ratio. Ion concentrations, determined by these control factors, play a decisive role in the development of strength. Generally, the strength is proportional to the BFS/FA ratio. The optimal values of the Na2 O/binder ratio of BFS-AAM and FA-AAM are between 5.5% and 8% and between 7 and 10%, respectively. The optimal values of the SiO2 /Na2 O ratio of BFS-AAM and FA-AAM are between 0.85 and 1.4 and between 0.6 and 1, respectively. Increasing the w/binder ratio will only benefit workability but will affect the strength negatively. A w/binder ratio of around 0.4 may strike a balance between strength and workability.